Modelling approach from cell to panel size for CIGS Solar utilizing Silvaco TCAD and Matlab Software - Hasani A.H.; Abdullah S.F.; Za'abar F.; Bahrudin M.S.; Mansor M.; Zuhdi A.W.M. (Akademi Sains Malaysia, 2023)
Conventionally, simulation and performance analysis of solar cells are conducted at cell level only. This paper presents a modelling approach that enables continuous performance evaluation of a solar cell from cell level to the system level. In the first stage of this work, a Cu(In, Ga)Se2 (CIGS) solar cell device structure is developed using Technology Computer-Aided Design (TCAD) software. In order to design a high-performance CIGS solar cell, material properties such as layer thickness and doping concentration are optimized with respect to the cells' efficiency within the ranges reported in the literature. Performance analysis of the TCAD model is then conducted and the electrical characteristics of the model are obtained. Matlab is used to post-process the electrical data in order to develop an equivalent one-diode electrical model from the TCAD model. The performance of the one-diode model in representing the TCAD model is validated at different temperatures and from the current-voltage (I-V) characteristic curves of both models, it is observed that the one-diode model is able to represent the TCAD model with great accuracy. The I-V curves coincide at the three main points such as the short-circuit current (Isc), the maximum power point (MPP), and the open-circuit voltage (Voc) with minimal error gaps along the I-V curve. As a conclusion, the one-diode model can be used in system-level simulations to observe the performance of the solar cell. 2019 Akademi Sains Malaysia.